Preliminary Study on the Echo-Assisted Intersphincteric Autologous Microfragmented Adipose Tissue Injection to Control Fecal Incontinence in Children Operated for Anorectal Malformations - Giovanni Parente; Valentina Pinto; Neil Di Salvo; Simone D'Antonio; Michele Libri; Tommaso Gargano; Vincenzo Davide Catania; Giovanni Ruggeri; Mario Lima (MDPI AG, 2020)
Aim of the study: To assess the efficacy of a novel technique (echo-assisted intersphincteric autologous microfragmented adipose tissue injection, also called "anal-lipofilling") in the management of non-responsive fecal incontinence in children born with anorectal malformations (ARMs). Methods: Following ethical committee approval (CHPED-MAR-18-02), anal-lipofilling was proposed to patients with fecal incontinence not responsive to medications or bowel management (bowel enema and/or transanal irrigation automatic systems), then a prospective study was conducted. Anal-lipofilling consisted of three phases: lipoaspiration from the abdominal wall, processing of the lipoaspirate with a Lipogems system and intersphincteric injection of the processed fat tissue via endosonographic assistance. A questionnaire based on Krickenbeck's scale (KS) was administered to the patients to evaluate the clinical outcome. Main Results: Four male patients (three recto-urethral fistula, and one recto-perineal fistula) underwent the anal-lipofilling procedure at a mean age of 13.0 ± 4.2 yrs. There were no complications during or after the procedure. From an initial assessment of the patients there was an improvement in the bowel function at a median follow up of 6 months, with better scores at KS (100% Soiling grade three pre-treatment vs. 75% grade one post-treatment). Conclusions: Even if our Study is preliminary, echo-assisted anal-lipofilling could be considered as a feasible and safe alternative technique in the management of the fecal incontinence in non-responding ARMs patients. More studies are still necessary to support the validity of the implant of autologous adipose tissue in the anal sphincter as a therapy for fecal incontinence in children born with ARMs.